Hubungan Antara Pemeriksaan Antibodi IgG Dengan Uji SGOT SGPT Pada Pasien Demam Berdarah Dengue Di RSU Sinar Kasih Purwokerto - Cici Farhana Ambarwanty Mohtar; Utami Pratyastiti Setyarini; Oksita Asri Widyayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by infection with the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito. The main clinical manifestations of this disease can be an increase in body temperature ≥ 38°C for 2 - 7 days, bleeding which is usually preceded by the appearance of red spots (petechiae), headache, joint pain accompanied by leukopenia, lymphadenopathy, thrombocytopenia and hemorrhagic diathesis. Liver dysfunction is one of the consequences of dengue infection that often occurs in patients. The liver is the target organ of the dengue virus which often appears in the form of hepatomegaly and a mild-moderate increase in aminotransferase enzyme levels although jaundice and acute liver failure are rare. Dengue patients have an increase in SGOT and SGPT levels. This study aims to determine whether there is a relationship between dengue IgG levels and SGOT and SGPT in Dengue Hemorrhagic Fever patients at RSU Sinar Kasih Purwokerto. The type of research used is an analytical study with a cross-sectional approach. Sampling was carried out using a consecutive sampling technique. Results were obtained from 100 samples with normal SGOT SGPT examination results, namely 10 patients and high results, namely 90 patients. The results of SGOT and SGPT examinations in dengue IgG positive patients increased >3 times which was included in category B and there was a significant relationship between SGOT and SGPT levels in Dengue IgG positive patients, with a p-value of 0.000, indicating a strong relationship between SGOT levels and SGPT with IgG examination results.